Continuum of Care - Building bridges between different phases of the patient's pathway - Michael Adolph; Marek Lichota (Clinical Nutrition Open Science)
Summary: The presented Continuum of Care concept refers to a patient-oriented care system describing a modern nutrition management workflow avoiding malnourished patients. For long time, nutrition has had low priority compared to resuscitation and other immediate therapies but does play an important role as malnutrition is associated with increased complications and delayed postoperative recovery. For optimal clinical outcomes, it is important to immediately start targeted nutritional therapy during severe illness. Continuum of care in a modern nutrition management starts with a diagnosis and the decision for surgery. It is an interdisciplinary approach involving different medical specialists. Ahead of surgical procedures, the patient´s condition is improved in the best possible way by means of a multimodal prehabilitation approach combining different interventions, e.g., exercise, patient education, psychologic support, and nutrition. This approach aims at strengthening the nutritional, physical as well as the psychological status of the patient. Addressing pre-operative risk factors significantly impacts the postoperative period. Patients actively participate in this process and receive supervision both before and during their hospital stay, as well as during discharge and the subsequent recovery and rehabilitation phase. Healthcare professionals should prioritize nutritional requirements. While guidelines on nutritional care exist, translating these guidelines into individualized nutritional plans is essential for providing optimal patient care. Thus, the presented Continuum of Care concept reflects an efficient, adapted nutritional therapy for patients throughout the whole course of their illness to fight malnutrition.